The Influence Of Airport Experience On Passenger Satisfaction And Behavioral Intentions (Case Study: Yogyakarta International Airport) - Zarra Isyana (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
airport has undergone a business transformation, from its previous focus solely on providing public facilities to becoming a multi-service provider by offering various activities, services, processes, and technologies that ultimately create an airport experience for passengers. As a result, airport management has begun implementing the concept of airport experience through the creation of desired passenger experience. The objective of study is analyse the factors of airport experience and its influence on passenger satisfaction, revisit intention, and positive word of mouth. A quantitative research approach was employed, and primary data collected from sample of 670 passengers at Yogyakarta International Airport through the use of online questionnaires. The research hypothesis tested using Structural Equation Modeling to determine whether the various factors related to airport experience have a positive influence on passenger satisfaction. The findings of the study indicate that security, airport facilities, serviscape, sense of place, finding way, and check-in have a positive influence on passenger satisfaction. Furthermore, passenger satisfaction also positively influences their intentions to revisit and their likelihood of spreading positive word-of-mouth information.